A near-infrared aggregation-induced luminescence material and its preparation method and application
By developing near-infrared aggregation-induced luminescence materials, using their aggregation-induced luminescence characteristics in latent fingerprint detection, the existing latent fingerprint detection methods are solved, and a high-resolution, fast, economical and harmless latent fingerprint detection effect is achieved.
Patent Information
- Application Number
- CN202211287222.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-10-20
AI Technical Summary
The existing latent fingerprint detection methods have problems such as complex operation, expensive equipment, and harmful to personnel and the environment, and lack a simple, fast, economical and harmless detection method.
A near-infrared aggregation-induced luminescent material was developed, and a near-infrared aggregation-induced luminescent material was constructed by connecting trianiline and isoquinoline as donor and acceptor modules, and a developer was sprayed with an atomizer to image the latent fingerprint.
High-resolution imaging of latent fingerprints is achieved, the development process is simple, fast, and low-cost, and is harmless to the detector and the environment.
Smart Images

Figure CN115536640B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of latent fingerprint detection, and in particular to a near-infrared aggregation-induced luminescence material and a preparation method and application thereof. Background Art
[0002] With the rapid development of optoelectronics, the fields of organic light-emitting materials, organic fluorescent probes, and bio-imaging agents have put forward higher and higher requirements for the luminescence performance in the aggregated state. In recent years, the emergence of aggregation-induced emission (AIE) materials has effectively solved the problem of luminescence quenching of organic light-emitting materials in the aggregated state, and realized its high-tech applications in the fields of energy, environment, and health. Aggregation-induced emission materials have become a new and important research direction in the fields of chemistry and materials.
[0003] There are a large number of sweat glands and sebaceous glands on the skin of human fingers, palms, and soles. People will constantly excrete sweat and sebum while undergoing metabolism. Therefore, when fingers and palms touch the surface of an object, they will leave invisible marks, which are called latent fingerprints. Its main components are water, inorganic salts, and organic matter. The sebum secreted by sebaceous glands includes fatty acids, glycerides, cholesterol, etc. Due to the uniqueness and lifelong invariance of human fingerprints, latent fingerprint development technology is widely used in criminal investigation cases, identification of disaster victims, security, security inspection, etc.; with the popularization of computer technology and the application of fingerprint recognition systems, fingerprint technology has been widely used in people's lives.
[0004] At present, there are three main methods for latent fingerprint extraction: the first is physical development method, such as smoke development method, iodine fumigation development method, metal deposition method, etc.; the second is chemical development method, such as silver nitrate method, ninhydrin method, DFO method, etc.; the third is optical development method, such as ultraviolet light inspection, laser inspection, Raman inspection, etc. However, these methods still have some shortcomings, such as the need for precise and expensive instruments, cumbersome operations, and the development process will cause harm to the inspectors and the environment. Therefore, it is urgent to develop a universal method for detecting latent fingerprints that is simple to operate, quick to respond, cost-effective, and non-destructive to the inspectors, the environment, and fingerprints. Summary of the invention
[0005] The purpose of the present invention is to provide a near-infrared aggregation-induced luminescence material with simple synthesis, readily available raw materials, high yield, non-toxicity, rapid reaction, and simple operation, as well as a preparation method and application thereof. The present invention introduces the property of aggregation-induced luminescence into the development of latent fingerprints, which firstly expands the application of AIE molecules, secondly makes the fingerprint imaging lines and detailed features clear, bright, and stable, and thirdly has low cost.
[0006] The implementation process of the present invention is as follows:
[0007] A near-infrared aggregation-induced luminescence material, the general structural formula of the near-infrared aggregation-induced luminescence material is as follows:
[0008]
[0009] Among them, π is selected from Any one of;
[0010] R is selected from an alkyl group having 1 to 4 carbon atoms, an alcohol alkyl group having 2 to 4 carbon atoms, or a -C n H 2n N + (CH3)3, wherein n=2, 3 or 4.
[0011] The preparation method of the above-mentioned near-infrared aggregation-induced luminescence material specifically uses triphenylamine and isoquinoline as donor and acceptor modules respectively, and connects them with a π bridge to construct the near-infrared aggregation-induced luminescence material.
[0012] Further, compound a, diphenylacetylene, silver tetrafluoroborate, copper acetate and rhodium catalyst are added to the reaction tube, and amine compounds and tert-butyl alcohol are added under nitrogen environment, refluxed at 90° C., and after the reaction is completed, the near-infrared aggregation-induced luminescence material is obtained after washing, extraction, separation and purification;
[0013] The structural formula of the compound a is
[0014] The amine compound is selected from alkylamines having 1 to 4 carbon atoms, alcohol alkylamines having 2 to 4 carbon atoms or C n H 2n N + (CH3)3Cl, wherein n=2, 3 or 4;
[0015]
[0016] Furthermore, the molar ratio of compound a, amine compound, diphenylacetylene, silver tetrafluoroborate, copper acetate and rhodium catalyst is 1:1.1:1.25:1:1:0.02; the specific process of washing, extracting, separating and purifying is washing with water and saturated brine, extracting the reaction liquid with dichloromethane, drying after separation, and purifying by column chromatography.
[0017] Further, the synthesis process of compound a is to add compound I, 4-triphenylamine boric acid, tetrakis(triphenylphosphine)palladium and potassium carbonate into a reaction bottle, add a mixed solvent of THF and H2O with a volume ratio of 3:1 under a nitrogen atmosphere, reflux at 85°C for 5h, add dichloromethane for extraction, separate and dry, and purify by column chromatography to obtain compound a;
[0018] The compound I is selected from any one of 4-(5-bromo-2-furan)benzaldehyde, 4-(5-bromo-2-thiophene)benzaldehyde or 4-(5-bromo-2-phenyl)benzaldehyde;
[0019]
[0020] Among them, π is selected from Any one of .
[0021] Furthermore, the molar ratio of the compound I, 4-triphenylamine boric acid, potassium carbonate and tetrakis(triphenylphosphine)palladium is 1:1.2:5:0.02.
[0022] Further, the synthesis process of compound a is to add 4-bromobenzaldehyde, N,N-diphenyl-4-vinylaniline, Bu4NBr and Pd(OAc)2 into a reaction flask and dissolve them in a mixed solvent of anhydrous DMF and toluene in a volume ratio of 1:1, add triethylamine to the obtained solution under a nitrogen atmosphere, heat the reaction mixture to 95°C, reflux overnight, filter and wash the solid with ethyl acetate after the reaction is completed, further wash the organic layer with a saturated saline solution, and dry over anhydrous Na2SO4, use petroleum ether / ethyl acetate in a volume ratio of 97:3 as an eluent, and purify the crude product by column chromatography to obtain compound a;
[0023] The molar ratio of 4-bromobenzaldehyde, N,N-diphenyl-4-vinylaniline, Bu4NBr and triethylamine is 1:1:2:2;
[0024]
[0025] Further, the synthesis process of compound a is to add 4-bromobenzaldehyde, PdCl2(PPh3)2, CuI, 4-acetylene-N,N-diphenylaniline and PPh3 into a reaction bottle, add toluene to dissolve under a nitrogen atmosphere, then drop diisopropylamine, heat and stir at 70°C for 4 hours, filter the reaction mixture and wash with ethyl acetate, evaporate the organic phase under reduced pressure, and then use pure hexane to hexane: dichloromethane in a volume ratio of 2:1 as an eluent, and purify the crude product by column chromatography to obtain compound a;
[0026] The molar ratio of 4-bromobenzaldehyde, PdCl2(PPh3)2, CuI, 4-acetylene-N,N-diphenylaniline and PPh3 is 1:0.04:0.04:1:0.02;
[0027]
[0028] The above-mentioned near-infrared aggregation-induced luminescence material is used as a developer in high-resolution imaging of latent fingerprints.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The present invention connects two aggregation-induced emission groups, triphenylamine and isoquinoline, through different π bridges. The single-bonded benzene rings in the molecule have a strong intermolecular torsional charge transfer (TICT) effect, which improves the luminescence performance of near-infrared aggregation-induced emission materials in an aggregated state. This type of molecule has a high affinity for fingerprint secretions, oils, etc., and has the characteristics of simple synthesis, mild reaction conditions, and good luminescence performance in an aggregated state.
[0031] (2) The present invention constructs a type of triphenylamine-π-isoquinoline near-infrared aggregation-induced luminescence material through the fluorescent materials of the above-mentioned donor, acceptor and bridge, and images latent fingerprints on materials such as tin foil and glass through atomizer spraying, effectively improving the imaging resolution of fingerprint development. This type of molecule can be used in multiple fields such as cell imaging and electroluminescent materials, and has a good market prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the latent fingerprint development effect of the developer TPA-1 on glass in Example 1;
[0033] Figure 2 This is the latent fingerprint development effect of the developer TPA-1 on the steel plate in Example 1;
[0034] Figure 3 This is the latent fingerprint development effect of the developer TPA-1 on the tile in Example 1;
[0035] Figure 4 This is the latent fingerprint development effect of the developer TPA-1 on tin foil in Example 1;
[0036] Figure 5 The detail effect of latent fingerprint development on tin foil using developer TPA-1 in Example 1;
[0037] Figure 6 This is the latent fingerprint development effect of the developer TPA-2 on the steel plate in Example 2;
[0038] Figure 7 This is the latent fingerprint development effect of the developer TPA-2 on leather in Example 2;
[0039] Figure 8 This is the latent fingerprint development effect of the developer TPA-2 on the tile in Example 2;
[0040] Fig. 9 This is the latent fingerprint development effect of the developer TPA-2 on tin foil in Example 2;
[0041] Fig.10The detail effect of latent fingerprint development on tin foil using developer TPA-2 in Example 2;
[0042] Fig.11 This is the latent fingerprint development effect of the developer TPA-3 on tin foil in Example 3;
[0043] Fig.12 This is the latent fingerprint development effect of the developer TPA-3 on glass in Example 3;
[0044] Fig.13 This is the latent fingerprint development effect of the developer TPA-3 on the tile in Example 3;
[0045] Fig.14 This is the latent fingerprint development effect of the developer TPA-3 on the steel plate in Example 3;
[0046] Fig.15 The detail effect of latent fingerprint development on tin foil using developer TPA-3 in Example 3;
[0047] Fig.16 It is the absorption spectra of fluorescent materials TPA-1, TPA-2 and TPA-3;
[0048] Fig.17 It is the normalized emission spectra of liquid fluorescent materials TPA-1, TPA-2 and TPA-3;
[0049] Fig.18 Normalized emission spectra of solid-state fluorescent materials TPA-1, TPA-2 and TPA-3. DETAILED DESCRIPTION
[0050] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented on the premise of the technical scheme of the present invention, and a detailed implementation method and specific operation process are given. The scope of the present invention is not limited to the following embodiments.
[0051] The fluorescent material of the present invention has excellent near-infrared luminescence performance in an aggregated state, has high affinity for fingerprint secretions, oils, etc., has the advantages of simple synthesis, mild reaction conditions, good luminescence performance in an aggregated state, etc., can be used to realize latent fingerprint imaging on various materials through atomizer spraying, and realize high-resolution imaging of the tertiary structure of fingerprints, achieving extremely high resolution.
[0052] Example 1 Fluorescent Material TPA-1
[0053] (1) Preparation of Compound 2:
[0054]
[0055] Compound 1 (365 mg, 1.45 mmol, 1.0 eq), 4-triphenylamine boronic acid (504 mg, 1.74 mmol, 1.2 eq), tetrakis(triphenylphosphine)palladium (35 mg, 0.029 mmol, 0.02 eq) and potassium carbonate (1 g, 7.26 mmol, 5 eq) were added to a 200 mL reaction bottle, and 60 mL of a mixed solvent of THF:H2O=3:1 (v:v) was added under a nitrogen atmosphere, refluxed at 85°C for 5 h, extracted with dichloromethane, dried after separation, and purified by column chromatography (eluent PE:EA volume ratio of 10:1) to obtain compound 2 (yield 365 mg, yield 60%) as a yellow solid. The structure of compound 2 is as follows:
[0056]
[0057] The above compound 1 is 4-(5-bromo-2-furan)benzaldehyde. Its synthesis process refers to CN201911223412.0 A triphenylamine co-sensitizer with a phenyl terminal bridge chain and its preparation method, which is synthesized by the method of step (1) of Example 1 in the patent.
[0058] The basic data of compound 2 are as follows:
[0059] Yellow solid
[0060] 1 H NMR (400MHz, CDCl3) δ9.99 (s, 1H), 7.90 (d, J = 8.4Hz, 2H), 7.84 (d, J = 8.4Hz, 2H), 7.62 (d, J = 8.7Hz, 2H), 7.2 9(t,J=8.2Hz,4H),7.15–7.10(m,6H),7.07(t,J=7.3Hz,2H),6.93(d,J=3.5Hz,1H),6.68(d,J=3.5Hz,1H).
[0061] 13 C NMR (100MHz, CDCl3) δ191.47,155.18,151.34,147.74,147.34,136.06,134.58,1 30.41,129.37,125.04,124.70,124.11,123.53,123.33,123.24,110.70,106.61.
[0062] HRMS(MALDI):m / z[M+H]+calcd for[C 29 H 21 NO2 + ]416.1651,found:416.1644.
[0063] (2) Preparation of fluorescent material TPA-1
[0064]
[0065] Compound 2 (188 mg, 0.45 mmol, 1.0 eq), diphenylacetylene (89 mg, 0.49 mmol, 1.1 eq), silver tetrafluoroborate (88 mg, 0.45 mmol, 1.0 eq), copper acetate (82 mg, 0.45 mmol, 1.0 eq) and rhodium catalyst (6 mg, 0.0009 mmol, 0.02 eq) were added to a 50 mL reaction tube, and 2 mol / L anhydrous ethylamine (0.3 mL, 0.56 mmol, 1.25 eq) and 10 mL tert-butanol were added under nitrogen atmosphere, refluxed at 90 ° C for 3 h, washed with water and saturated brine, extracted with dichloromethane, dried after separation, and purified by column chromatography (eluent dichloromethane: methanol volume ratio of 20:1) to obtain red solid TPA-1 (yield 140 mg, yield = 43%), the specific structure is as follows:
[0066]
[0067] The basic data of fluorescent material TPA-1 are as follows:
[0068] Red solid
[0069] 1 H NMR (400MHz, Acetone) δ10.04(s,1H),8.63(d,J=8.8Hz,1H),8.46(d,J=12.2Hz,1H),7.84(d,J=3.3Hz,1H),7.67–7.57(m,4H),7.45(dd,J =4.6,1.8Hz,3H),7.41(m,2H),7.36(dd,J=15.0,6.4Hz,8H),7.16–7.08(m,6H),7.02(m,3H),4.65(q,J=7.2Hz,2H),1.59(t,J=7.3Hz,3H).
[0070] 13C NMR (100MHz, CDCl3) δ157.18,150.17,148.99,148.42,147.14,144.12,138.74,138.46,138.02,133.31,132.19,130.87,130.20,130. 14,129.45,128.85,128.70,128.48,126.73,126.41,125.32,124.95,123.64,122.98,122.77,117.63,114.89,107.33,54.82,16.86.
[0071] HRMS(MALDI):m / z[M+H]+calcd for[C 45 H 35 N2O+]619.2744, found:619.2748.
[0072] Experiment on the color development of latent fingerprints using fluorescent material TPA-1
[0073] Prepare an aqueous solution of a developer. Dissolve TPA-1 in an ethanol solution, add an appropriate amount of water to prepare an aqueous solution with a concentration of 50 μmol / L, and use the prepared solution for subsequent latent fingerprint development. TPA-1 is the fluorescent developer of the present invention.
[0074] Preparation of fingerprint samples: Before collecting fingerprint samples, volunteers washed their hands, then touched their oily parts (forehead or nose area) with their hands, gently massaged to evenly cover the surface with grease, and gently pressed the surface of glass, steel plate, tile, and tin foil with the greased fingers.
[0075] Place the developer aqueous solution in a small atomizer and atomize it towards the object with fingerprints for 1 minute. Irradiate with a 365nm ultraviolet lamp. Use a microscope to filter (the filter transmits light with a wavelength of 530nm or more) and take photos. A relatively clear second-level and third-level structure of the fingerprint can be obtained. The substrates are glass, steel plate, tile, and tin foil, and the first-level structure, second-level structure, and third-level structure on the tin foil are shown. See Figure 1-5 .
[0076] Example 2 Fluorescent Material TPA-2
[0077] (1) Preparation of Compound 3
[0078] The process and parameters of step (1) are similar to those of step (1) of Example 1, except that the raw materials are different, the raw material is 4-(5-bromo-2-thiophene)benzaldehyde, and the product is
[0079] The synthesis process of 4-(5-bromo-2-thiophene)benzaldehyde is described in the literature: Jelena Konstantinovi′c, Milica Videnovi′c, Jelena Srbljanovi′c, et.al,. Antimalarials with Benzothiophene Moieties as Aminoquinoline Partners. Molecules 2017, 22(3), 343.
[0080] (2) Preparation of fluorescent material TPA-2
[0081]
[0082] Compound 3 (270 mg, 0.63 mmol, 1.0 eq), diphenylacetylene (123 mg, 0.69 mmol, 1.1 eq), silver tetrafluoroborate (122 mg, 0.63 mmol, 1.0 eq), copper acetate (114 mg, 0.63 mmol, 1.0 eq) and rhodium catalyst (8 mg, 0.012 mmol, 0.02 eq) were added to a 50 mL reaction tube, and 2 mol / L anhydrous ethylamine (0.4 mL, 0.78 mmol, 1.25 eq) and 10 mL tert-butanol were added under nitrogen atmosphere, refluxed at 90 ° C for 3 h, washed with water and saturated brine, extracted with dichloromethane, dried after separation, and purified by column chromatography (eluent dichloromethane: methanol volume ratio of 20: 1) to obtain red solid TPA-2 (310 mg, yield = 68%), the specific structure is as follows:
[0083]
[0084] The basic data of fluorescent material TPA-2 are as follows:
[0085] Red solid
[0086] 1H NMR (400MHz, CDCl3) δ10.00 (s, 1H), 8.61 (d, J = 8.7Hz, 1H), 8.09 (d, J = 8.7Hz ,1H),7.62(s,1H),7.45–7.40(m,3H),7.39–7.35(m,3H),7.35–7.31(m,3H), 7.31–7.24(m,6H),7.19(d,J=3.9Hz,1H),7.15(dd,J=6.5,2.8Hz,2H),7.11 (d,J=7.8Hz,4H),7.04(m,3H),4.60(q,J=7.2Hz,2H),1.53(t,J=7.2Hz,3H).
[0087] 13 C NMR (100MHz, CDCl3) δ149.14,148.92,148.41,147.10,144.28,142.71,139.13,138.62,138.48,133.22,132.26,130.83,130.22,130.17, 130.14,129.43,128.89,128.84,128.74,128.54,128.46,126.74,12 6.63,126.51,124.94,123.87,123.65,122.75,119.78,54.96,16.77.
[0088] HRMS(MALDI):m / z[M] + Calculate for [C 45 H 36 N2S + ]635.2593,found:635.2515.
[0089] Experiment on the color development of latent fingerprints using fluorescent material TPA-2
[0090] Prepare an aqueous solution of a developer. Dissolve TPA-2 in an ethanol solution, add an appropriate amount of water to prepare an aqueous solution with a concentration of 50 μmol / L, and use the prepared solution for subsequent latent fingerprint development. TPA-2 is the fluorescent developer of the present invention.
[0091] Preparation of fingerprint samples: Before collecting fingerprint samples, volunteers washed their hands, then touched their oily parts (forehead or nose area) with their hands, gently massaged to evenly cover the surface with grease, and gently pressed the surface of steel plates, leather, tiles, and tin foil with the greased fingers.
[0092] Place the developer aqueous solution in a small atomizer and atomize it towards the object with fingerprints for 1 minute. Irradiate with a 365nm ultraviolet lamp. Use a microscope to filter (the filter transmits light with a wavelength of 530nm or more) and take photos. A relatively clear second-level and third-level structure of the fingerprint can be obtained. The substrates are steel plate, leather, tile, and tin foil, and the first-level structure, second-level structure, and third-level structure on the tin foil are shown. See Figure 6-10 .
[0093] Example 3 Fluorescent Material TPA-3
[0094] (1) Preparation of Compound 4
[0095] The process and parameters of step (1) are similar to those of step (1) of Example 1, except that the raw materials are different, the raw material is 4-(5-bromo-2-phenyl)benzaldehyde, and the product is
[0096] Among them, the synthesis process of 4-(5-bromo-2-phenyl)benzaldehyde is referenced in: Zhi Huang, Bo Wang, Qing Zhang, et al., Highly twisted bipolar emitter for efficient nondoped deep-blue electroluminescence. Dyes and Pigments, 2017, 140, 328-336.
[0097] (2) Preparation of fluorescent material TPA-3:
[0098]
[0099] Compound 4 (125 mg, 0.29 mmol, 1.0 eq), diphenylacetylene (58 mg, 0.32 mmol, 1.1 eq), silver tetrafluoroborate (58 mg, 0.29 mmol, 1.0 eq), copper acetate (54 mg, 0.29 mmol, 1.0 eq) and rhodium catalyst (10 mg, 0.016 mmol, 0.05 eq) were added to a 50 mL reaction tube, and 2 mol / L anhydrous ethylamine (0.2 mL, 0.32 mmol, 1.1 eq) and 10 mL tert-butanol were added under nitrogen atmosphere, refluxed at 90 ° C for 3 h, washed with water and saturated brine, extracted with dichloromethane, dried after separation, and purified by column chromatography (eluent dichloromethane: methanol volume ratio of 20:1) to obtain red solid TPA-3 (94 mg, yield = 91%), the specific structure is as follows:
[0100]
[0101] The basic data of fluorescent material TPA-3 are as follows:
[0102] Red solid
[0103] 1 H NMR (400MHz, CDCl3) δ10.19(s,1H),8.78(d,J=8.7Hz,1H),8.20(dd,J=8.7,1.4Hz,1H), 7.78(s,1H),7.66(d,J=8.4Hz,2H),7.60(d,J=8.4Hz,2H),7.47(d,J=8.7Hz,2H),7.38( dd,J=5.0,1.9Hz,3H),7.32(m,3H),7.29(m,6H),7.17(dd,J=6.6,3.0Hz,2H),7.13(dd, J=8.2,2.4Hz,6H),7.05(t,J=7.3Hz,2H),4.68(q,J=7.2Hz,2H),1.56(t,J=7.3Hz,3H).
[0104] 13 C NMR (100MHz, CDCl3) δ149.94,149.55,147.97,147.42,144.07,142.16,139.19,138.30,136.48,133.25,133.05,132.36,130.76, 130.58,130.23,130.11,129.37,128.89,128.78,128.59,128.28,127.67,127.39,126.76,124.77,123.32,122.86,55.21,16.90.
[0105] HRMS(MALDI):m / z[M] + Calculate for [C 47 H 37 N2 + ]629.2951,found:629.2954.
[0106] Experiment on the color development of latent fingerprints using fluorescent material TPA-3
[0107] Prepare an aqueous solution of a developer. Dissolve TPA-3 in an ethanol solution, add an appropriate amount of water to prepare an aqueous solution with a concentration of 50 μmol / L, and use the prepared solution for subsequent latent fingerprint development. TPA-3 is the fluorescent developer of the present invention.
[0108] Preparation of fingerprint samples: Before collecting fingerprint samples, volunteers washed their hands, then touched their oily parts (forehead or nose area) with their hands, gently massaged to evenly cover the surface with grease, and gently pressed the surface of tin foil, glass, tile, and steel plate with the greased fingers.
[0109] Place the developer aqueous solution in a small atomizer and atomize it for 1 minute on the object with fingerprints. Irradiate with a 365nm ultraviolet lamp. Use a microscope to filter (the filter transmits light with a wavelength of 530nm or more) and take photos. You can get a clearer fingerprint 2nd and 3rd level structure. The substrates are tin foil, glass, tile, and steel plate, and the 1st, 2nd, and 3rd level structures on tin foil are shown. Figure 11-15 .
[0110] Example 4
[0111] (1) 4-Bromobenzaldehyde (1 g, 5.4 mmol, 1.0 eq), N,N-diphenyl-4-vinylaniline (1.5 g, 5.4 mmol, 1.0 eq), Bu4NBr (3.5 g, 10.8 mmol, 2.0 eq) and Pd(OAc)2 (71 mg, 0.432 mmol, 0.08 eq) were dissolved in 50 mL of a mixed solvent of anhydrous DMF and toluene, wherein the volume ratio of anhydrous DMF to toluene was 1:1. Under a nitrogen atmosphere, triethylamine (1.5 mL, 10.8 mmol, 2.0 eq) was added dropwise and heated under reflux at 95 °C overnight. After the reaction was completed, the solid was filtered and washed with ethyl acetate. The organic layer was further washed with saturated saline solution and dried over anhydrous Na2SO4. The crude product was purified by column chromatography using petroleum ether:ethyl acetate in a volume ratio of 97:3 as the eluent to obtain an orange-red solid (yield 82%).
[0112]
[0113] (2) The process and parameters are similar to those of step (2) in Example 1, except that the anhydrous ethylamine added in molar ratio is replaced by anhydrous methylamine; and the raw material added in molar ratio is replaced by the product obtained in step (1) of this example. The structure of the final product is as follows:
[0114]
[0115] Example 5
[0116] (1) Same as step (1) of Example 4.
[0117] (2) The same as step (2) of Example 1, the raw materials are replaced by The final product structure is
[0118] Example 6
[0119] (1) Same as step (1) of Example 4.
[0120] (2) The process and parameters are similar to those of step (2) in Example 1, except that the anhydrous ethylamine added in molar ratio is replaced by anhydrous ethanolamine; and the raw material added in molar ratio is replaced by the product obtained in step (1) of this example. The structure of the final product is as follows:
[0121]
[0122] Example 7
[0123] (1) Same as step (1) of Example 4.
[0124] (2) The process and parameters are similar to those of step (2) in Example 1, except that the anhydrous ethylamine added in molar ratio is replaced by 3-amino-N,N,N-trimethylpropane-1-ammonium chloride; and the raw material added in molar ratio is replaced by the product obtained in step (1) of this example. The structure of the final product is as follows:
[0125]
[0126] Example 8
[0127] (1) 4-Bromobenzaldehyde (98.8 mg, 0.54 mmol, 1.0 eq), PdCl2(PPh3)2 (14.0 mg, 0.02 mmol, 0.04 eq), CuI (3.8 mg, 0.02 mmol, 0.04 eq), 4-ethynyl-N,N-diphenylaniline (145.3 mg, 0.54 mmol, 1.0 eq) and PPh3 (5.2 mg, 0.02 mmol, 0.04 eq) were dissolved in 15 mL of toluene under nitrogen atmosphere, and then 10 mL of diisopropylamine was added dropwise. After stirring and heating at 70°C for 4 h, the reaction mixture was filtered and washed with ethyl acetate (repeated three times with 15 mL each time). The organic phase was evaporated under reduced pressure and then purified by gradient elution with pure hexane to hexane: dichloromethane (volume ratio 2:1) as the eluent to obtain a yellow solid (yield 163.2 mg, yield 81%).
[0128]
[0129] (2) The process and parameters are similar to those of step (2) in Example 4, except that the raw materials added in molar ratio are replaced by the product obtained in step (1) of this example. The structure of the final product is as follows:
[0130]
[0131] Example 9
[0132] (1) Same as step (1) of Example 8.
[0133] (2) The process and parameters are similar to those of step (2) in Example 1, except that the raw materials added in molar ratio are replaced by the product obtained in step (1) of this example. The structure of the final product is as follows:
[0134]
[0135] Example 10
[0136] (1) Same as step (1) of Example 8.
[0137] (2) The process and parameters are similar to those of step (2) in Example 1, except that the anhydrous ethylamine added in molar ratio is replaced by anhydrous ethanolamine; and the raw material added in molar ratio is replaced by the product obtained in step (1) of this example. The structure of the final product is as follows:
[0138]
[0139] Embodiment 11
[0140] (1) Same as step (1) of Example 8.
[0141] (2) The process and parameters are similar to those of step (2) in Example 1, except that the anhydrous ethylamine added in molar ratio is replaced by 3-amino-N,N,N-trimethylpropane-1-ammonium chloride; and the raw material added in molar ratio is replaced by the product obtained in step (1) of this example. The structure of the final product is as follows:
[0142]
[0143] Since the synthesis process of Examples 12-20 is similar to that of Example 1, the differences are listed in the table below.
[0144] Table 1 Differences between Examples 12-20 and Example 1 during the synthesis process
[0145]
[0146]
[0147] The parameters and experimental procedures not mentioned in the above table are the same as the corresponding steps of Examples 1-3.
[0148] In the experiment of developing the latent fingerprint by the fluorescent material of the present invention, the operating temperature can be selected between 0-50°C, the atomization time of the substrate with the fingerprint can be selected between 1s-120s, and the concentration of the fluorescent material as a developer can be selected between 10μmol / L-100μmol / L, preferably 30μmol / L-60μmol / L. The excitation light is 350-550nm, and the excitation light is preferably 365nm. The solvent used for preparing the developer is a mixed solvent of ethanol and water, preferably ethanol: water = 1:100 (v:v). Before irradiation with ultraviolet light, the developer stays on the latent fingerprint for 10s-5min, preferably 30s-2min of development time, and after staying for a period of time, it is irradiated with ultraviolet light again, so that the latent fingerprint on the substrate can show bright fluorescence. With the help of ultraviolet light and a microscope, a clearly visible latent fingerprint can be obtained, and the tertiary structure of the latent fingerprint can be seen. The experiment of developing the color of latent fingerprints by the fluorescent materials obtained in the above-mentioned Examples 4-20 is the same as the experimental process of developing the color of latent fingerprints by the fluorescent material TPA-1 obtained in Example 1, and will not be described in detail.
[0149] The present invention utilizes fluorescent materials to enable rapid and convenient latent fingerprint development, and can develop latent fingerprints clearly without causing significant damage to the latent fingerprints. The fluorescent materials of the present invention can specifically identify latent fingerprints and have almost no background fluorescence under ultraviolet light.
[0150] Absorption wavelength test of fluorescent materials TPA-1, TPA-2 and TPA-3.
[0151] The fluorescent materials TPA-1, TPA-2 and TPA-3 were dissolved in THF to prepare 1×10 -5 The solution of M was scanned by UV-visible spectrophotometer (Puxi) in the range of 300-700 nm. The spectrum was processed by Origin to obtain the absorption spectra of fluorescent materials TPA-1, TPA-2 and TPA-3, see Fig.16 As can be seen from the figure, the fluorescent materials TPA-1, TPA-2 and TPA-3 in the solution state have absorbance at 350-550nm. The excitation light required for fingerprint development can be selected from the wavelength range of 350-550nm, so the more common wavelength of 365nm is selected as the experimental wavelength.
[0152] Emission wavelength test of fluorescent materials TPA-1, TPA-2 and TPA-3.
[0153] The fluorescent materials TPA-1, TPA-2 and TPA-3 were dissolved in THF to prepare 1×10 -5The emission spectra of the solutions of TPA-1, TPA-2 and TPA-3 were tested by fluorescence spectrophotometer (Eclipse) with excitation wavelengths of 420 nm, 480 nm and 490 nm, respectively, and scanning ranges of 420-800 nm, 500-900 nm and 500-900 nm, respectively. The spectra were processed by Origin to obtain the normalized emission spectra of the liquid fluorescent materials TPA-1, TPA-2 and TPA-3, see Fig.17 As can be seen from the figure, the maximum emission wavelength of the liquid fluorescent material TPA-1 is between 600 and 700 nm, the maximum emission wavelength of the liquid fluorescent material TPA-2 is between 600 and 700 nm, and the maximum emission wavelength of the liquid fluorescent material TPA-3 is between 500 and 550 nm.
[0154] The fluorescent materials TPA-1, TPA-2 and TPA-3 solids were placed on the Hamamatsu Fluorescence Lifetime / Transient Absorption Analysis System (Hamamatsu Quantaurus-Tau C11367-35) respectively, with an excitation wavelength of 500nm, and the normalized emission spectra of the solid fluorescent materials TPA-1, TPA-2 and TPA-3 were tested, see Fig.18 As can be seen from the figure, the maximum emission wavelengths of solid-state fluorescent materials TPA-1 and TPA-2 are between 650 and 750 nm, and the maximum emission wavelength of solid-state fluorescent material TPA-3 is between 600 and 650 nm. The maximum emission wavelength determines the luminescent color of the compound. The longer the maximum emission wavelength, the redder the luminescent color of the compound. The luminescent color on the fingerprint is theoretically closer to the solid emission spectrum. Figure 5 , Fig.10 and Fig.15 From the color, we can find that the emission colors of TPA-1 and TPA-2 are more red than that of TPA-3.
[0155] pass Fig.18 When taking photos with a microscope, use a transmission filter to filter out light before 530nm and pass light with a wavelength above 530nm.
[0156] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and the specific implementation of the present invention cannot be limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. A near-infrared aggregation-induced emission material, characterized in that: The general structural formula of the near-infrared aggregation-induced luminescence material is as follows: Among them, π is selected from Any one of; R is selected from an alkyl group having 1 to 4 carbon atoms, an alcohol alkyl group having 2 to 4 carbon atoms, or —C n H 2n N + (CH3)3Cl, wherein n=2, 3 or 4.
2. The method for preparing the near-infrared aggregation-induced emission material according to claim 1, characterized in that: Add compound a, diphenylacetylene, silver tetrafluoroborate, copper acetate and rhodium catalyst into a reaction tube, add amine compounds and tert-butyl alcohol under nitrogen environment, reflux at 90° C., and after the reaction, wash, extract, separate and purify to obtain a near-infrared aggregation-induced luminescence material; The structural formula of the compound a is The amine compound is selected from alkylamines having 1 to 4 carbon atoms, alcohol alkylamines having 2 to 4 carbon atoms or C n H 2n N + (CH3)3Cl, wherein n=2, 3 or 4; 3. The method for preparing the near-infrared aggregation-induced emission material according to claim 2, characterized in that: The molar ratio of compound a, amine compound, diphenylacetylene, silver tetrafluoroborate, copper acetate and rhodium catalyst is 1:1.1:1.25:1:1:0.02; the specific process of washing, extracting, separating and purifying is washing with water and saturated brine, extracting the reaction liquid with dichloromethane, drying after separation, and purifying by column chromatography.
4. The method for preparing the near-infrared aggregation-induced emission material according to claim 2, characterized in that: One of the synthesis processes of compound a is to add compound I, 4-triphenylamine boric acid, tetrakis(triphenylphosphine)palladium and potassium carbonate into a reaction flask, add a mixed solvent of THF and H2O in a volume ratio of 3:1 under a nitrogen atmosphere, reflux at 85°C for 5h, add dichloromethane for extraction, separate and dry, and purify by column chromatography to obtain compound a; The compound I is selected from any one of 4-(5-bromo-2-furan)benzaldehyde, 4-(5-bromo-2-thiophene)benzaldehyde or 4-(5-bromo-2-phenyl)benzaldehyde; Among them, π is selected from Any one of; The second synthesis process of compound a is to add 4-bromobenzaldehyde, N,N-diphenyl-4-vinylaniline, Bu4NBr and Pd(OAc)2 into a reaction flask and dissolve them in a mixed solvent of anhydrous DMF and toluene in a volume ratio of 1:1, add triethylamine to the obtained solution under a nitrogen atmosphere, heat the reaction mixture to 95°C, reflux overnight, filter and wash the solid with ethyl acetate after the reaction is completed, further wash the organic layer with a saturated saline solution, and dry it over anhydrous Na2SO4, use petroleum ether / ethyl acetate in a volume ratio of 97:3 as an eluent, and purify the crude product by column chromatography to obtain compound a; The molar ratio of 4-bromobenzaldehyde, N,N-diphenyl-4-vinylaniline, Bu4NBr and triethylamine is 1:1:2:2; The third step of the synthesis process of compound a is to add 4-bromobenzaldehyde, PdCl2(PPh3)2, CuI, 4-acetylene-N,N-diphenylaniline and PPh3 into a reaction bottle, add toluene to dissolve under a nitrogen atmosphere, then drop diisopropylamine, heat and stir at 70°C for 4 hours, filter the reaction mixture and wash with ethyl acetate, evaporate the organic phase under reduced pressure, and then use pure hexane to hexane: dichloromethane in a volume ratio of 2:1 as an eluent, and purify the crude product by column chromatography to obtain compound a; The molar ratio of 4-bromobenzaldehyde, PdCl2(PPh3)2, CuI, 4-acetylene-N,N-diphenylaniline and PPh3 is 1:0.04:0.04:1:0.02; 5. The method for preparing the near-infrared aggregation-induced emission material according to claim 4, characterized in that: The molar ratio of the compound I, 4-triphenylamine boric acid, potassium carbonate and tetrakis(triphenylphosphine)palladium is 1:1.2:5:0.
02.
6. Use of the near-infrared aggregation-induced luminescence material according to claim 1 as a developer in high-resolution imaging of latent fingerprints.
Citation Information
Patent Citations
A triphenylamine cosensitizer with phenyl-terminated bridging chain and its preparation method
CN111100099B
AIE luminogens for visualization and treatment of cancer
CN107849441A
Fluorescent viscosity probes with aggregation-induced luminescence properties
CN107936945A
